PENGARUH WARNA PADA IKLAN MEDIA CETAK TERHADAP MEMORI CALON KONSUMEN - Anwar, Fathul (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
Abstract This research aims is to examine the influence of color on print advertising against consumers memory. The research design used is posttest only control group design. The collection of data in this study using memory test. Parametric analysis techniques were used to test the hypothesis is independent sample t test to test the difference between 50 subject in experimental group and 50 subject in control group. The result t-test analysis in the control group and experimental group shown the value p = 0,000 (p<0,01) which means that there are very significant differences in memory experimental group with control group of advertisements that have been presented. It mean that the rate of memory against the advertisements that have been presented at the experimental group was higher than control group. These results indicate that the hypothesis was accepted. Keyword: memory, color, print advertising.